CLINICAL EFFICACY OF INFRA POPLITEAL ANGIOPLASTY FOR BELOW THE KNEE PERIPHERAL VASCULAR OCCLUSIVE DISEASE - Usman, Rashid; Mazhar, Minahil; Fatima, Rabail; Jamil, Muhammad; Majeed, Shahid (Journal of Ayub Medical College Abbottabad, 2023)
Background: Peripheral arterial disease (PAD) affects a substantial proportion of the global population, particularly older individuals, affecting around 200 million people worldwide highlighting its significant impact on human health. Critical limb ischemia (CLI) is the most severe clinical presentation of PAD characterized by ischemic rest pain tissue ulceration or gangrene. The objective of the study is to assess the efficacy of infra popliteal angioplasty (in terms of wound healing and limb salvage) in patients with below-the-knee total chronic occlusion (TCO). Methods: In this cross-sectional study, all consecutive patients in one year with TCO and fulfilling the inclusion criteria were included. Results: A total of 64 limbs underwent angioplasty. The mean age was 55.38 ± 13.12 (Range 22-88) years and there were 73% (n=47) males. Diabetes mellitus was the most prevalent risk factor in 59.4% (n=38) of patients. 48.4 % (n=31) of patients had below-knee TCO in all three arteries. Technical Success was achieved in 95.3% (n=61/64). All 3 patients who had technical failure ended up with below-the-knee amputation. Furthermore, 2 more patients who had technical success also ended up with below-the-knee amputation. The difference between these two rates was significant (100% vs 3.3%; p-value =0.004). In terms of wound healing, statistically significant improvement was noted within the first 6 months (p-value = 0.05). The limb salvage rate was 90.6% (n=59/64). The primary patency rate was 81.3% (n=52) and 76.6% (n=49) at 6 and 12 months respectively. Conclusion: Angioplasty results in statistically significant wound healing leading to a higher limb salvage rate, in patients with TCO of infrapopliteal arteries.